1989
DOI: 10.1136/sti.65.6.382
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis: prevalence in outpatients, association with some micro-organisms and laboratory indices.

Abstract: SUMMARY Seven hundred and ninety three women were investigated, aged between 16 and 78 years, to evaluate the prevalence of bacterial vaginosis (BV) and some associated micro-organisms, and to discuss the significance of laboratory indices correlated to this pathology. BV was diagnosed on the basis of four distinct criteria: a positive result of the test for amines with 10% KOH (odour-test), the presence of clue cells on fresh microscopic examination, a pH > 4 5 and direct Gram stain positive (the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 28 publications
2
29
0
1
Order By: Relevance
“…Further, between 93 and 100% of women suffering from bacterial vaginosis were heavily colonized by G. vaginalis (8,18,65,89,92,94,167,170,226), and the numbers of CFU in samples from diseased vaginas were much higher than in healthy vaginas according to most (5,182,213,219,233), but not all (25,137), authors. As expected, the finding of a negative G. vaginalis culture had a 97% predictive value for exclusion of bacterial vaginosis (5,46). 17) were important in focusing attention on the joint roles of anaerobes and G. vaginalis in the disease process, and their findings have been amply confirmed (16,26,168,216).…”
Section: Significance Of G Vaginalis Inmentioning
confidence: 78%
See 3 more Smart Citations
“…Further, between 93 and 100% of women suffering from bacterial vaginosis were heavily colonized by G. vaginalis (8,18,65,89,92,94,167,170,226), and the numbers of CFU in samples from diseased vaginas were much higher than in healthy vaginas according to most (5,182,213,219,233), but not all (25,137), authors. As expected, the finding of a negative G. vaginalis culture had a 97% predictive value for exclusion of bacterial vaginosis (5,46). 17) were important in focusing attention on the joint roles of anaerobes and G. vaginalis in the disease process, and their findings have been amply confirmed (16,26,168,216).…”
Section: Significance Of G Vaginalis Inmentioning
confidence: 78%
“…G. vaginalis and Mobiluncus spp. were found together in cultures from one-third of women with vaginosis (46,94).…”
Section: Significance Of G Vaginalis Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Current studies have found the prevalence of BV among non-pregnant women to range from 15-30% and up to 50% of pregnant women have been found to have bacterial vaginosis. [3][4][5][6] Bacterial vaginosis is diagnosed by various methods. These methods are Amsels criteria, Gram stain (Nugent score/Hay Ison grading), Bacterial vaginosis blue test which measures vaginal fluid sialidase activity.…”
Section: Introductionmentioning
confidence: 99%